Inong Bale Fort As A Symbol Of The Strength Of Aceh's Maritime Women - Azkia Arufa; Munawiah Abdullah; Marduati Mukhtar; Husaini Husda (SEUNEUBOK LADA: Jurnal ilmu-ilmu Sejarah, Sosial, Budaya dan Pendidikan, 2026)
This study aims to present the active involvement of women in the defense system of the Aceh Sultanate from the sixteenth to the early seventeenth century, particularly within a maritime context. The article examines the role of Acehnese women in maritime defense dynamics, analyzes the strategic function of Inong Bale Fort as part of the coastal defense system, and explains its significance as a symbol of women’s strength, courage, and resilience. This research employs a qualitative approach using field observation, in-depth interviews, and documentation studies conducted in Gampong Lamreh, Aceh Besar Regency. The data obtained were analyzed using a descriptive-interpretative approach, employing maritime archaeology and gender theory in historiography to understand the social, military, and symbolic roles of women in the context of Acehnese history.. The findings indicate that Inong Bale Fort functioned not only as a coastal defense structure against maritime threats but also as a center for training, organization, and management of the Inong Bale women troops under the leadership of Admiral Malahayati. The existence of this fort demonstrates that Acehnese women held a strategic and significant position within the military and maritime systems of the Aceh Sultanate, while also challenging historiographical narratives that have traditionally privileged male-centered perspectives.